2015
DOI: 10.1111/febs.13343
|View full text |Cite
|
Sign up to set email alerts
|

Rigidity versus flexibility: the dilemma of understanding protein thermal stability

Abstract: The role of fluctuations in protein thermostability has recently received considerable attention. In the current literature a dualistic picture can be found: thermostability seems to be associated with enhanced rigidity of the protein scaffold in parallel with the reduction of flexible parts of the structure. In contradiction to such arguments it has been shown by experimental studies and computer simulation that thermal tolerance of a protein is not necessarily correlated with the suppression of internal fluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
198
3
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 237 publications
(212 citation statements)
references
References 117 publications
9
198
3
2
Order By: Relevance
“…Still, it cannot be excluded that some of these distinctive amino acid residues contribute to the lower responsiveness of these spores to the AGFK mixture. Notably, the same unique amino acids might simultaneously cause reduced functionality and higher thermostability of these GRs, as a decreased conformational flexibility that is characteristic for thermostable proteins has been suggested to compromise their activities (68,69). Potentially stabilizing amino acid changes, such as substitutions to L-alanine, which tend to stabilize ␣-helices (70,71), or to hydrophobic amino acids, which can increase a degree of protein packing (72), can be found in the GR subunits of the investigated high-heat-resistant strains (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…Still, it cannot be excluded that some of these distinctive amino acid residues contribute to the lower responsiveness of these spores to the AGFK mixture. Notably, the same unique amino acids might simultaneously cause reduced functionality and higher thermostability of these GRs, as a decreased conformational flexibility that is characteristic for thermostable proteins has been suggested to compromise their activities (68,69). Potentially stabilizing amino acid changes, such as substitutions to L-alanine, which tend to stabilize ␣-helices (70,71), or to hydrophobic amino acids, which can increase a degree of protein packing (72), can be found in the GR subunits of the investigated high-heat-resistant strains (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the presence of flexibility could also increase the substrate binding affinity (Liu, Tao, Meng, Fu, & Zhang, 2011) The stability of a protein is widely believed to arise from its decreased flexibility, implying an inverse correlation between the stability and flexibility (Kamerzell & Middaugh, 2008;Karshikoff, Nilsson, & Ladenstein, 2015). However, more and more experimental studies and computer simulations argue against a simple inverse relationship between decreased stability and increased flexibility, and it is now common to find observations showing proteins with both low stability and flexibility (Bouvignies et al, 2005;Ferreon, Volk, Luxon, Gorenstein, & Hilser, 2003;Karshikoff et al, 2015;LeMaster, Tang, Paredes, & Hernández, 2005;Reuveni, Granek, & Klafter, 2008). With regard to the nsSNP-derived mutations, a number of studies have demonstrated that there is no obvious inverse correlation between protein stability and flexibility upon mutations (Kamerzell & Middaugh, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…43,44 A relationship often exists between thermodynamic stability and the structural dynamics of a protein, such that thermostable proteins require higher temperatures for equivalent functional dynamics compared to their mesophile counterpart. 45,46 Thus, a Cys-free mutant form of FGF-1 that retains overall WT stability and dynamics is desirable. In this regard, the C16S/A66C/C117A/P134A mutant is only slightly more stable than WT FGF-1 and possesses a very similar EPD profile.…”
Section: Discussionmentioning
confidence: 99%